Desenvolvimento de uma tecnologia alternativa para a desidratação de lodos provenientes da biodigestão anaeróbia de resíduos orgânicos domésticos - Scalcon, Araceli (2014)
Recent research has shown that the organic fraction of municipal solid waste and industrial can be treated through the process of digestion. These processes produce two types of products, biogas and sludge resulting from the digestion. The last one has a great potential for use as fertilizer, however, to ensure the quality of the product, is necessary a process for dehydration/drying it. In this context, the objective of this work was the development of an alternative technology for dewatering sludge from the digestion process. For this purpose, the methodology included conducting seven steps: 1) study to identify relevant variables, steps and parameters of the drying process of sludge; 2) characterization of the source of sludge; 3) qualitative and quantitative characterization of sludge; 4) analysis of the conventional methods, processes and technologies to dewatering sludge from digestion ; 5) develop/propose an alternative technology for the dehydration of sludge from the digestion; 6) building a prototype and operational tests/performance to analysis of the developed technology. The result of the study was an alternative technology with 10 attributes, the most relevant being the maximization of the use of solar energy, the convective effect of ultraviolet rays to microbiological inactivation, minimizing the influence of rainfall, ease of feeding and pullout of dewatered sludge with maximum efficiency (reduction of 96% moisture content). Alternative technology prevails in a simultaneous filtration system and solar drying techniques whose characteristics meet the requirements of patentability (novelty requirement, inventive step, and industrial application descriptive adequacy).